Determination of Favourite Market for 3D-Printer Product Based Online Platform - Pasmawati, Yanti; Tontowi, Alva Edy; Hartono, Budi; Wijayanto, Titis (International Review of Management and Marketing, 2018)
The growth of the online market lately is very rapid due to the World Wide Web. Many crowdfunding-based companies are helping creative projects grow rapidly. To measure the success of a project based solely on the percentage of fundraising cannot represent the favourite market of the desired product backers. In this study, the measure of success is judged by the ratio of the funding amount and the ratio of the product amount in the period of time. After this, there are 4 quadrants that determine the success of the product including: moderate favourite markets (quadrant I), the most favourite markets (quadrant II), not favourite markets (quadrant III), and moderate favourite markets (quadrant IV). Eight companies start-up with 68 selected 3D Printer products in this study. The results show that no single product is in "favourite market". 63 products are in "non-favourite markets". There are only 5 projects in the market "moderate favourites". Keywords: online platform, favourite market, crowdfunding JEL Classifications: L260, M130, M310 https://doi.org/10.32479/irmm.6906